2016
DOI: 10.1089/scd.2015.0384
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel EZH2 Targets Regulating Osteogenic Differentiation in Mesenchymal Stem Cells

Abstract: Histone three lysine 27 (H3K27) methyltransferase enhancer of zeste homolog 2 (EZH2) is a critical epigenetic modifier, which regulates gene transcription through the trimethylation of the H3K27 residue leading to chromatin compaction and gene repression. EZH2 has previously been identified to regulate human bone marrow-derived mesenchymal stem cells (MSC) lineage specification. MSC lineage specification is regulated by the presence of EZH2 and its H3K27me3 modification or the removal of the H3K27 modification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 61 publications
3
51
0
1
Order By: Relevance
“…Moreover, EZH2 was shown to function as a repressor of osteogenic differentiation through the direct methylation of genes critical for osteogenic lineage specification. More recently, bioinformatic analyses of gene expression and ChIPseq data sets of human MSC osteogenic differentiation revealed several novel Ezh2 target molecules mediating MSC osteogenesis (41). Although some of these genes (summarized in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, EZH2 was shown to function as a repressor of osteogenic differentiation through the direct methylation of genes critical for osteogenic lineage specification. More recently, bioinformatic analyses of gene expression and ChIPseq data sets of human MSC osteogenic differentiation revealed several novel Ezh2 target molecules mediating MSC osteogenesis (41). Although some of these genes (summarized in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed the gene expression patterns of known Ezh2 target genes regulated during human MSC osteogenic differentiation (41) in long-bone samples collected from wild-type and newborn Ezh2 2/2 mice. The data showed that most of these genes (with the exception of FHFL1) were significantly upregulated in the long bones of Ezh2-null mice compared with wild-type controls, correlating to an increase in the expression of osteogenesis inductive factors such as Bmp2 and Runx2 (Fig.…”
Section: Assessment Of Known Ehz2 Target Genes In Ezh2-deficient Micementioning
confidence: 99%
“…Studies on the EZH2 null mutation in chondrocytes (using the COL2a1‐Cre driver) revealed that EZH2 deficiency reduces H3K27me3 levels, yet remarkably had minimal impact on skeletal development or maturation of articular cartilage . Nevertheless, EZH2 target gene analysis in either osteoblasts or chondrocytes revealed that EZH2 enhances expression of osteogenic markers in chondrocytes, including BMP2 and BMP2 responsive transcription factors SP7 and extracellular matrix proteins (e.g., IBSP and BGLAP) as well as a large number other targets that have been identified in MSCs . However, EZH1 partially compensates for loss of EZH2 during skeletal development.…”
Section: The Basics Of Epigeneticsmentioning
confidence: 99%
“…Of note, several studies have demonstrated that Ezh2 is an essential regulator of bone formation through modulating the osteogenic differentiation of MSCs (Chen et al., 2016; Hemming et al., 2016, 2017). Additionally, Li et al.…”
Section: Discussionmentioning
confidence: 99%